Secondary School Mathematics Teachers' Views of Manipulatives and Their Use in the Classroom - Jones, Adrian (Université d'Ottawa / University of Ottawa, 2010)
Mathematical manipulative materials (manipulatives) invite students to explore and represent abstract mathematical concepts in varied, concrete, tactile, and visually rich ways. Considering the prominence of the use of mathematical manipulatives in current K-12 curricula, pedagogical resources and professional development, research studies show that few secondary school teachers use them. While these studies do not examine this issue from the teachers’ perspective, they posit that some teachers lack the mathematical knowledge connected to manipulatives, are uncomfortable with or uncertain how to use them, or do not believe that manipulatives have value in the teaching of secondary school mathematics. As a result there is a great need for research that provides further detail as to why and how secondary school mathematics teachers use manipulatives in their classrooms. This study, guided by the research questions: ‘How do secondary school teachers view the use of manipulatives in teaching mathematics?’ and ‘How do secondary school teachers describe their use of manipulatives in teaching mathematics?’, sought to examine these issues through semi-structured interviews with six secondary school mathematics teachers. This study supports the notion that the use of manipulatives in secondary school mathematics classrooms is influenced by teachers' views and experience with manipulatives. It highlights some of the challenges that teachers face, and supports from which they gain confidence and competence in their efforts to integrate the use of mathematical manipulatives into their teaching practice.
Keywords: use of manipulatives; secondary school; mathematical manipulatives